PENGARUH VIDEO PENDEK TERHADAP PEMEROLEHAN BAHASA KEDUA PADA ANAK - Salsabila Askia; Yansen Yehuda Tarigan; Sundawati Tisnasari (Jurnal Bastra (Bahasa dan Sastra), 2026)
This research looks at how shorts video affect children's second language acquisition. Analysis methods and english data collection were used in this descriptive qualitative research. A nine-year-old child who enjoys watching shorts video was the subject of this study. Children can benefit from shorts video as an educational resource. Shorts video allow children to learn on their own while being supervised by adults. The information collected includes vocabulary development of verbs, adjectives, adverbs and nouns. As well as the negative and positive impacts of second language acquisition due to the influence of shorts video.